Status Hukum Pekerja Yang diangkat Menjadi Anggota Direksi pada Perseroan Terbatas Tanpa Adanya Pengakhiran Perjanjian Kerja - Bima Nuranda; Anita Afriana; Holyness N Singadimedja (Faculty of Law Hang Tuah University, 2019)
The appointment of a director in a Limited Liability Company can be chosen from its own workers. In reality, this raises a legal problem when the worker appointed to the Board of Directors is dismissed by the General Meeting of Shareholders (GMS), while the termination has been regulated in Law Number 40 of 2007 concerning Limited Liability Companies, but when workers appointed as members of the board of directors do not accept such dismissals, the aforementioned directors choose to submit the fulfillment of their workers’ rights as stipulated in Law Number 13 of 2003 concerning Employment. From this problem, it can be inferred that there is a lack of clarity regarding the legal status of a worker who is appointed as a board of directors through GMS and the legal consequences when the worker appointed as director is dismissed.